Aspects of leadership : ethics, law, and spirituality - Connelley, Carroll J.; Tripodi, Paolo, 1965-; Marine Corps University (U.S.). Press (Quantico, Virginia Marine Corps University Press, 2012)
"The essays in this book are intended to inform leaders, and the general public, about the challenges of ethical decision making, the application of the law of war, and the important role of spirituality. Aspects of Leadership will educate readers and generate important questions that leaders should ask themselves, encouraging them to reflect upon their pivotal roles in these three areas" --Back cover
Foreword -- Acknowledgments -- Introduction / Carroll Connelley -- ETHICS: Leadership, ethics and culture in COIN operations: case examples from Marjeh, Afghanistan / Brian Christmas and Paula Holmes-Eber ; Ethics and irregular warfare: the role of the stakeholder theory and care ethics / Geoffroy Murat ; A pedagogy of practical military ethics / Clinton A. Culp ; Leadership in a world of blurred responsibilities
"1st printing, 2012" --Title page verso
Includes bibliographical references and index
Keywords: Military ethics; Leadership; Command of troops; Military art and science -- Moral and ethical aspects